2019
DOI: 10.1007/s11250-019-01982-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of gastrointestinal helminths and their impact in commercial small-scale chicken flocks in the Mekong Delta of Vietnam

Abstract: Commercial small-scale chicken farms managed as all-in-all-out but operating with low standards of hygiene/biosecurity are increasingly common in Vietnam. These conditions facilitate the transmission of gastrointestinal helminths. However, there are no published data on helminths in these systems. We aimed (1) to determine the prevalence/burden of gastrointestinal helminths in small-scale commercial flocks in the Mekong Delta region and (2) to investigate the association between worm burdens and birds' weight … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The present investigation revealed a high prevalence (67.2%) of colonization with gastrointestinal helminths, the most common species being the nematodes H. gallinarum and A. galli . A recent study in the same area reported a higher burden of A. galli in diseased chickens than in healthy ones ( Van et al., 2019 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present investigation revealed a high prevalence (67.2%) of colonization with gastrointestinal helminths, the most common species being the nematodes H. gallinarum and A. galli . A recent study in the same area reported a higher burden of A. galli in diseased chickens than in healthy ones ( Van et al., 2019 ).…”
Section: Discussionmentioning
confidence: 93%
“…A number of bacteria such as Pasteurella multocida ( Mariana and Hirst, 2000 ), Avibacterium paragallinarum ( Chukiatsiri et al., 2010 ), and Mycoplasma gallisepticum ( Fujisawa et al., 2019 ) have all been reported to circulate in Southeast Asia. The low standards of hygiene and biosecurity typical of small-scale chicken farms in the area also facilitate the presence of gastrointestinal helminth burdens in these flocks ( Van et al., 2019 ). However, most studies to date have typically focused on single etiological agents, and the investigation of a wider panel of pathogens is required to prioritize disease control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, poultry production is making a significant and increasing contribution to the national economy of most countries ( Dube et al., 2010 ; Adang et al., 2014 ; Ferdushy et al., 2016 ). However, the production performance of poultry can be significantly reduced because of various intestinal helminth parasites ( Permin et al., 1997 ; Ruff, 1999 ; Ogbaje et al., 2012 ; Adang et al., 2014 ; Bachaya et al., 2015 ; Van et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main explanatory factors for the losses identified were a small flock size and high mortality. The (high) observed cumulative mortality (median 18%) is likely to reflect a high incidence of bacterial, viral and parasitic diseases identified in the area (Carrique-Mas et al, 2019b; Nguyen T. B. Van et al, 2020; Nguyen Thi Bich Van et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chicken production in the area is predominantly semi-intensive (including backyard and small-scale), and is typically based on slow-growing native breeds (Duc and Long, 2008; Lan Phuong et al, 2015). Production is however hampered by a high incidence of parasitic (Nguyen T. B. Van et al, 2020), viral and bacterial diseases (Nguyen Thi Bich Van et al, 2020), often resulting in high mortality losses (Carrique-Mas et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%